Literasi Kebencanaan melalui Pendekatan Partisipatif dalam Edukasi Mitigasi Bencana Pada Rute Kritis Kawasan Wisata - I Dewa Made Alit Karyawan; Made Mahendra; Ratna Yuniarti; Ida Ayu Oka Suwati Sideman; Jauhar Fajrin; I Wayan Yasa; Hasyim Hasyim; Rohani Rohani; I Dewa Gede Jayanegara; Humairo Saidah (LPPPM STAI Darul Hikmah Bangkalan, 2026)
Pakuan Village is a tourist village with the potential for waterfalls and road access through hilly areas that have high disaster vulnerability. Risks such as landslides, flash floods, and slippery roads threaten the safety of the public and tourists. The main problem is the low literacy of community disaster preparedness and the limited understanding of mitigation in road infrastructure. This service activity aims to increase knowledge and awareness through disaster mitigation education. The methods used include participatory socialization, material delivery, and evaluation through pre-test and post-test. The results show an increase in public understanding of the types of disasters, how they impact road infrastructure, and simple mitigation measures that can be taken. Mitigation education has proven to be effective in increasing community preparedness and is the first step in building a disaster awareness culture in the Pakuan Village tourist area.